2013
DOI: 10.1080/1936928x.2013.837419
|View full text |Cite
|
Sign up to set email alerts
|

Violent Death Among Recently Released Prison Inmates: Stories Behind the Numbers

Abstract: Research on rates of violent deaths in prison releasees exists, however little work has gone into examining their associated contexts and circumstances. Using North Carolina Department of Corrections and North Carolina Violent Death Reporting System data, the authors sought to understand the contexts surrounding the deaths of recently released inmates. Findings revealed that homicides (64% of deaths) were associated with violence as a result of argument and with criminal activity. Suicides (30%) were in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For example, several studies found that demographic and circumstantial details in the narratives were insufficient for case identification and characterization of death incidents. (Scheyett et al 2013 ; Frazier et al 2017 ; Briker et al 2019 ; Fraga Rizo et al 2021 ) Sensitive topics such as child maltreatment, intimate partner homicides, and legal intervention deaths, while routinely collected by the NVDRS, are limited to the information provided by the source documents and interpretations of the abstractors. (Lord 2014 ; Brown and Seals 2019 ; Hunter et al 2022 ) The second challenge relates to information variation within the NVDRS system, such as discrepancies between different data sources (e.g., C/ME and LE reports) and variations in reporting, coding, abstraction, completeness, and contents of text narratives and NVDRS across states.…”
Section: Resultsmentioning
confidence: 99%
“…For example, several studies found that demographic and circumstantial details in the narratives were insufficient for case identification and characterization of death incidents. (Scheyett et al 2013 ; Frazier et al 2017 ; Briker et al 2019 ; Fraga Rizo et al 2021 ) Sensitive topics such as child maltreatment, intimate partner homicides, and legal intervention deaths, while routinely collected by the NVDRS, are limited to the information provided by the source documents and interpretations of the abstractors. (Lord 2014 ; Brown and Seals 2019 ; Hunter et al 2022 ) The second challenge relates to information variation within the NVDRS system, such as discrepancies between different data sources (e.g., C/ME and LE reports) and variations in reporting, coding, abstraction, completeness, and contents of text narratives and NVDRS across states.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse criminological studies have shown evidence that both homicide offending and victimization are often an outgrowth of a lifestyle that is reflective of a broader involvement in various antisocial acts (Behnken et al, 2011;Drury and DeLisi, 2011;Loeber et al, 2017;Trulson et al, 2012). For instance, Scheyett et al (2013) tracked mortality patterns of felons recently released from prison in the Eastern USA and found that 64 percent of the violent deaths of prison releasees were homicides. The homicides primarily occurred as the result of an altercation that was part of ongoing criminal activity.…”
Section: Homicide and Criminal Lifestylementioning
confidence: 99%
“…To date, only one study, which included adults released from prison in the US, has examined the circumstances of violence-related death among people involved in the criminal justice system [ 5 ]. This study found that common circumstances included being involved in a crime, or an argument with a person known to the deceased, before death [ 5 ]. To our knowledge, no previous studies have examined the circumstances of violence-related deaths among justice-involved young people.…”
Section: Introductionmentioning
confidence: 99%